Detecção de faltas entre espiras em geradores de fase dividida: uma abordagem baseada em morfologia matemática - Sartori, Angelo Felipe (2021)
The stator of Synchronous Generator is susceptible to different types of failures, short circuits and abnormal operating conditions. Among the defects, we can mention the single-phase, two-phase, threephase faults and turn-to-turn. This last one, in many cases, is the reason of other more serious faults. Synchronous Generator Protection against turn-to-turn faults is not well explored. The majority of the protections methods found are applied to generators with two or three parallel windings per phase. As the number of windings per phase increases, it becomes more difficult to detect this type of defect. Thus, this work presents a cutting-edge methodology for detecting turn-to-turn fault split phase synchronous generators, based on Mathematical Morphology. This technique allows to work with the signals in the time domain, using the existing current and potential transformer on the machine. In order to verify the reliability of the developed method, several tests were carried out, including turn-to-turn faults in synchronous generators, signals with noise, load variation and different fault inception angle and external faults to the generator. Two used machine models, one cylindrical pole with two windings per phase and another salient pole with six windings per phase. To assess the possibility in real applications, some tests were simulated in real time using the concept software-in-the-loop. The real-time digital simulator used was MODELO DO SIMULAODOR from OPAL-RT. To finish the test stage, a comparative analysis, between several traditional schemes and the proposed one was made. Besides, the methology was tested for a real case of turn-to-turn fault While traditional protection schemes can detect faults between turns up to XX%, the developed method detects failures with small winding suppression, regardless of the machine model and loading. In addition, the proposed methodology uses known electrical quantities, that is, it requires only one current and potential transformer per phase.